The Relationship between Healthy Lifestyle Compliance and Quality of Life in Hypertension Patients - Emi Eliya Astutik; Irwina Angelia Silvanasari; Roby Aji Permana (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Hypertension negatively impacts the quality of life of its sufferers. A healthy lifestyle is essential for managing hypertension. This study aims to analyze the relationship between adherence to a healthy lifestyle and quality of life in people with hypertension. Methods: This quantitative study involved 80 randomly selected hypertensive patients. The study variables encompassed compliance with healthy lifestyle practices and the overall quality of life, measured using a valid and reliable healthy lifestyle adherence questionnaire and the WHOQOL-BREF. Bivariate analysis was performed using the Gamma test. Results: The study found that 41.25% were non-adherent to a healthy lifestyle, and 41.25% also had a poor quality of life. The findings of the study demonstrated a strong association between commitment to a healthy lifestyle and quality of life among individuals with hypertension, supported by a p-value of 0.000 and a correlation coefficient (r) = 0.859. Conclusions: Hypertensive individuals who maintain healthy lifestyle practices typically demonstrate better quality of life. This suggests that it is essential for people with hypertension to be motivated to live healthily by increasing physical activity, following a balanced diet, and avoiding tobacco use.